Urheberrechtssysteme und kollektive Rechtwahrnehmung in Südosteuropa - Mesevic, Iza Razija (Abhandlungen zum Urheber- und Kommunikationsrecht, 2015)
"This publication provides a view beyond the big European collective management organisations (CMOs) and contributes to the transparency of the collective rights management systems of young and prospective EU-Member States. Since the accession of Slovenia and Bulgaria, the territory of EU expands over the region of South-Eastern Europe (SEE). Nevertheless, the EU academic circles are generally unfamiliar with the field of collective management of copyright and related rights in SEE. However, in the last twenty years, a diverse and to an extent rather specific landscape of CMOs has been developed in that region. The legal framework and the particularities of the latter are worthy of scientific consideration. This book also deals with the position of those CMOs from the region with regard to the increasingly strong requirement for cross-border licensing in the online field and the tendency for more competition between CMOs."